HAVEARBEJDE: Moralsk praksis i en sydafrikansk storby - Jørgensen, Nanna Jordt (Tidsskriftet Antropologi, 2005)
Ten years after democratization, the township areas surrounding South African cities are still dominated by poverty and unemployment. For most township inhabitants, wage employment is not an option, and they engage in numerous activities to provide their families with the daily bread. One of these activities is the cultivation of vegetables in community gardens. In Port Elizabeth, community garden projects have received support from a number of development institutions working in the townships. Development institutions and township inhabitants alike regard cultivation as not just a matter of putting food on the table, but also an activity with significant moral connotations. To the township inhabitants, the moral person is a person who continuously participates in social networks through everyday exchanges with family and neighbours, and ritual exchanges with their forefathers. Cultivation of the soil provides cultivators with crops for those exchanges and creates a feeling of being close to the forefathers. Furthermore, cultivators underline that morality becomes embodied through hard work, which teaches people good social behaviour. Development institutions, on the other hand, see the moral person as an autonomous individual who works hard to sustain his family and develop and thus proves himself as a good citizen. While development institutions expect cultivators to concentrate their efforts on making the gardens productive and sustainable projects, the cultivators use cultivation as an investment in social relations and focus on the sustainability of their life as such. In this way, cultivators’ practice is also a way of reworking and reinterpreting the meaning of a development intervention to fit a local moral world.